2021
DOI: 10.3390/cells10092408
|View full text |Cite
|
Sign up to set email alerts
|

Role of ERLINs in the Control of Cell Fate through Lipid Rafts

Abstract: ER lipid raft-associated protein 1 (ERLIN1) and 2 (ERLIN2) are 40 kDa transmembrane glycoproteins belonging to the family of prohibitins, containing a PHB domain. They are generally localized in the endoplasmic reticulum (ER), where ERLIN1 forms a heteroligomeric complex with its closely related ERLIN2. Well-defined functions of ERLINS are promotion of ER-associated protein degradation, mediation of inositol 1,4,5-trisphosphate (IP3) receptors, processing and regulation of lipid metabolism. Until now, ERLINs h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 138 publications
0
11
0
Order By: Relevance
“…Previous studies found that Erlin1 could form a complex with Erlin2, which could play an important role in cholesterol binding, lipid metabolism regulation, and influencing liver fat deposition [ 46 , 47 ]. Both Erlin1 and Erlin2 play pivotal roles in controlling cell fate by regulating lipid metabolism [ 48 ]. Another study demonstrated that Erlin1 interacting with AMBRA1 at mitochondria-associated membranes raft-like microdomains is essential for autophagosome formation [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found that Erlin1 could form a complex with Erlin2, which could play an important role in cholesterol binding, lipid metabolism regulation, and influencing liver fat deposition [ 46 , 47 ]. Both Erlin1 and Erlin2 play pivotal roles in controlling cell fate by regulating lipid metabolism [ 48 ]. Another study demonstrated that Erlin1 interacting with AMBRA1 at mitochondria-associated membranes raft-like microdomains is essential for autophagosome formation [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, from this point of view, autophagy is also to be considered as a crucial process capable of promoting cancer survival under metabolic and genotoxic stress, endowing cancer cells with resistance to treatment, even if some support an ambivalent role of autophagy in cancer [ 29 , 69 , 70 , 71 ]. In this regard, some papers have suggested an involvement of autophagy in resistance to apoptosis and in some cases autophagy and apoptosis have been found to be inversely correlated [ 72 , 73 , 74 ]. The antiapoptotic role of NGB against oxidative stress, as well as other hypothetical functions of this globin, seems to be linked to the set of factors of expression, localization and interaction of NGB with other proteins [ 15 , 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Across these two studies of maternal depression, the gene Erlin2 was identified as a differentially expressed imprinted gene by Litzky et al and as being adjacent to four differentially methylated CpG sites by Lund et al [ 44 , 45 ]. Although a placental specific role for this gene is unknown, its protein is known to be localized to the endoplasmic reticulum where it has functions in protein degradation and lipid metabolism [ 56 ]. Maternal socioeconomic position (SEP) has been associated with placental methylation of 33 CpGs (FDR < 0.1) in 426 participants from the Extremely Low Gestational Age Newborns (ELGAN) study [ 47 ].…”
Section: Placental Epigenomics and Prenatal Exposuresmentioning
confidence: 99%